Variability of physical parameters along the east coast of peninsular Malaysia and gulf of Thailand due to the northeast monsoon - Lim You Rang (Universiti Putra Malaysia Terengganu, 2014)
This study will provide additional information on the research on the variation of physical properties along the east coast of Peninsular Malaysia and Gulf of Thailand due to the northeast monsoon.